2013
DOI: 10.1038/ng.2657
|View full text |Cite
|
Sign up to set email alerts
|

The duck genome and transcriptome provide insight into an avian influenza virus reservoir species

Abstract: The duck (Anas platyrhynchos) is one of the principal natural hosts of influenza A viruses. We present the duck genome sequence and perform deep transcriptome analyses to investigate immune-related genes. Our data indicate that the duck possesses a contractive immune gene repertoire, as in chicken and zebra finch, and this repertoire has been shaped through lineage-specific duplications. We identify genes that are responsive to influenza A viruses using the lung transcriptomes of control ducks and ones that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
279
4
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(307 citation statements)
references
References 45 publications
(56 reference statements)
13
279
4
5
Order By: Relevance
“…Since the caspase-like activity is strongly downregulated upon the r e p l a c e m e n t o f c o n s t i t u t i v e p r o t e a s o m e s b y immunoproteasomes in the mouse and human (Groettrup et al 1996), the absence of such a change when comparing proteasome from the chicken brain and spleen already strongly suggests that no immunoproteasome is present in the chicken spleen, bursa of Fabricius, or thymus. After the duck genome was reported last year, we blasted the available sequences for the immunosubunits β1i, β2i, and β5i as well as the thymus-specific subunit β5t, but these subunits were not detectable as already reported for Galliformes and zebra finch (Huang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Since the caspase-like activity is strongly downregulated upon the r e p l a c e m e n t o f c o n s t i t u t i v e p r o t e a s o m e s b y immunoproteasomes in the mouse and human (Groettrup et al 1996), the absence of such a change when comparing proteasome from the chicken brain and spleen already strongly suggests that no immunoproteasome is present in the chicken spleen, bursa of Fabricius, or thymus. After the duck genome was reported last year, we blasted the available sequences for the immunosubunits β1i, β2i, and β5i as well as the thymus-specific subunit β5t, but these subunits were not detectable as already reported for Galliformes and zebra finch (Huang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…About 30% of the sequence reads could be aligned to the bovine genome, a closely-related species. The study of Jonker et al (2012) used the same technique to identify SNPs in the Barnacle Goose (Branta leucopsis) by aligning 1.77 million reads to the Mallard (Anas platyrhynchos) genome (divergence time 30 million years) (Huang et al, 2013). In that study, 16.1% of the reads successfully aligned, subsequently allowing the identification of 2188 high confidence SNPs.…”
Section: Model Species Reference Genome and Snp Validationmentioning
confidence: 99%
“…Paired end reads {lOObp) were mapped to the Mallard (Anas platyrhynchos) genome, version 73 (Huang et al, 2013, supplemen tary material) using SMALT (http://www.sanger.ac.uk/re sourcesfsoftwarefsmalt/). Previous research indicated that SMALT is appropriate for mapping paired end reads when the reference genome is distantly related to the sampled species (Frantz et al, 2013 ).…”
Section: Processing Sequencesmentioning
confidence: 99%